Mental health interprofessional education for health professions students: bridging the gaps. Issue 1 (8th April 2014) - McAllister, Margaret; Statham, Dixie; Oprescu, Florin; Barr, Nigel; Schmidt, Teressa; Boulter, Christine; Taylor, Penny; McMillan, Jo; Jackson, Shauna; Raith, Lisa
Abstract : Purpose: – Government-run mental health services in Australia run predominantly on a multidisciplinary team (MDT) model. Literature and observation from practice shows that interprofessional tertiary sector training is absent, ad hoc or not documented, leaving students inadequately prepared for disciplinary differences in opinions and practices. Learning in interprofessional educational settings provides one way of overcoming the difficulties. The purpose of this paper is to describe the outcomes of an interprofessional learning experience targeting final year Australian students enroled in health promotion, registered nursing, enroled nursing, paramedic science, psychology, social work and occupational therapy who are intending to work in mental health teams. Design/methodology/approach: – Using a mixed method, pre- and post-test design (four time intervals), with data collected from three scales and open-ended questions, this study measured participant changes in knowledge and attitudes towards interprofessional education and mental health. The study also examined students' and educators' perceptions of the value of an interprofessional teaching and learning model. Findings: – There was a significant increase in clinical confidence at each time interval, suggesting that the intervention effects were maintained up to three months post-training. Themes about the value of interprofessional learning in mental health were extracted from student data: learning expanded students' appreciation for difference; this in turn expanded students' cross-disciplinary communication skills; growing appreciation for diverse world views was seen to be relevant to person-centred mental healthcare; and practice articulating one's own disciplinary views clarified professional identity. Research limitations/implications: – Generalisability of the outcomes beyond the disciplines sampled in this research is limited. MDTs typically include doctors, but we were unable to include medical students because the university did not offer a medical programme. The readiness for participation in a collaborative MDT approach may differ among students groups, disciplines and universities and technical and further educations. There may also be differences not accounted for in these findings between undergraduate students and established healthcare professionals. Further research needs to establish whether the findings are applicable to other student groups and to professionals who already work within MDTs. Originality/value: – These results demonstrate that intensive interprofessional learning experiences in tertiary education can be effective means of increasing students' awareness of the role of other professionals in MDT.